2016
DOI: 10.1194/jlr.m065458
|View full text |Cite
|
Sign up to set email alerts
|

EPA prevents fat mass expansion and metabolic disturbances in mice fed with a Western diet

Abstract: The authors acknowledge the staff from Auvergne University Experimental Animal Laboratory and Christophe Del’Homme, Philippe Denis, Anne Terisse-Lottier and Alexandre Teynie from the Experimental Animal Facility of the Human Nutrition Unit (INRA of Clermont-Ferrand) for their assistance throughout the animal protocol. We thank Celine Bobby for her help for TaqMan gene expression assays. We gratefully acknowledge financial support and doctoral fellowship (to A.P.) fromLesieur and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 41 publications
8
42
4
Order By: Relevance
“…The preventative studies with pure EPA ethyl esters challenge some previous findings in this area of study. Earlies studies have reported a reduction in fat mass with EPA-enriched oils, which we did not observe 43,44 . Perhaps the differences in results lies in the concentration and purity of EPA and the timing as well as duration of intervention.…”
Section: Discussioncontrasting
confidence: 72%
“…The preventative studies with pure EPA ethyl esters challenge some previous findings in this area of study. Earlies studies have reported a reduction in fat mass with EPA-enriched oils, which we did not observe 43,44 . Perhaps the differences in results lies in the concentration and purity of EPA and the timing as well as duration of intervention.…”
Section: Discussioncontrasting
confidence: 72%
“…Consumption of a high‐fat diet (HFD) rich in saturated fatty acids leads to obesity and metabolic disorders [ 4 ] while intake of polyunsaturated fatty acids (PUFAs) may promote a metabolically healthy phenotype. [ 5,6 ] Typically, marine n‐3 PUFAs, notably eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have been shown to reduce IR in rodents possibly by regulating the secretion of adipocytokines, [ 7–9 ] dampening the inflammatory process, [ 10–12 ] inhibiting adipose tissue remodeling, [ 13 ] and promoting mitochondrial function and fatty acid oxidation. [ 14 ] However, whether marine n‐3 PUFAs are able to reverse the established IR in the context of obesity remains unclear since existing studies mainly assessed the preventative effect on progressive IR.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] However, whether marine n‐3 PUFAs are able to reverse the established IR in the context of obesity remains unclear since existing studies mainly assessed the preventative effect on progressive IR. In addition, since only a few studies have applied individual n‐3 PUFAs (EPA and DHA), [ 9,10 ] their individual effect and mechanisms involved have poorly been understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, hsl was found to be divided into two types in C. idella , including hsla and hslb (Sun et al ., ). In M. musculus , EPA was observed to increase the gene expression of atgl (Pinel et al ., ). Analogously, EPA enhanced C. idella adipocytes lipolysis by upregulating the (m)RNA levels of atgl and hsl (Liu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, hsl was found to be divided into two types in C. idella, including hsla and hslb (Sun et al, 2016). In M. musculus, EPA was observed to increase the gene expression of atgl (Pinel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%